A context-aware framework for CSCW applications in enterprise environments - Lima, Christopher (2013)
Future pervasive environments will take into consideration physical and digital social relationships. Nowadays it is important to use collective intelligence, where the interpretation of context information can be harnessed as input for context-aware applications, especially for group collaboration. For collaborative applications this represents opportunities, but also new challenges in terms of using collective information for adaptability and personalization in pervasive environments. This paper presents the challenges in design and development of a context-aware framework CSCW supporting pro-behaviour capabilities in pervasive communities.